Method for manufacturing positive electrode active material for lithium secondary battery using waste positive electrode active material
Lithium reoxygenated materials are prepared by grinding and spray-drying the positive electrode active material of the waste lithium-ion secondary battery, which solves the problems of high costs and environmental pollution in traditional methods, and achieves efficient and environmentally friendly reuse of positive electrode active material.
Patent Information
- Application Number
- JP2025001837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-24
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, when manufacturing the positive electrode active material of lithium ion secondary batteries, there are problems of high production costs and environmental pollution, especially the traditional co-precipitation method leads to low material utilization efficiency.
By using the positive electrode active material of the discarded lithium-ion secondary battery as the raw material, and through mixing, grinding, spray drying and heat treatment, lithium reoxygenated materials with electrochemical substances and stability similar to traditional methods were prepared.
It realizes efficient recycling and reuse of positive electrode active materials, reduces production costs, reduces environmental pollution, and improves the electrochemical substances and stability of the materials.
Smart Images

Figure 2025039670000011 
Figure 2025039670000012 
Figure 2025039670000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material, and more specifically, to a method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material, which can improve electrochemical characteristics and stability by controlling the specific surface area of the waste positive electrode active material. [Background technology]
[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.
[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries, and composite oxides such as LiCoO2, LiMn2O4, LiNiO2, and LiMnO2 have been studied as examples. Recently, oxides in which part of the nickel in the lithium composite oxide is replaced with metals such as Co, Mn, and / or Al have been proposed. In particular, ternary lithium composite oxides typically containing Ni, Co, and Mn or Ni, Co, and Al are mainly used for large-capacity lithium secondary batteries for electric vehicles. There have also been attempts to improve the electrochemical properties and stability of the positive electrode active material by doping the ternary lithium composite oxides with additional elements.
[0005] As technology advances, the demand for lithium secondary batteries, including for electric vehicles, is rapidly increasing. In the meantime, there is a growing demand in related industries to reduce the costs of lithium secondary batteries and the various materials used in the batteries.
[0006] For example, in the past, a co-precipitation method has been generally used to synthesize a precursor of a lithium composite oxide containing ternary or more elements. However, the co-precipitation method generates a large amount of wastewater and is considered to be a cause of environmental pollution due to complicated process steps, as well as a cause of increased manufacturing costs of positive electrode active materials.
[0007] As a result, research has been conducted recently to reduce the manufacturing costs of positive electrode active materials by recycling waste positive electrode active materials recovered from lithium secondary batteries that have reached the end of their service life. Summary of the Invention [Problem to be solved by the invention]
[0008] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is driving the market, while the demand for positive electrode active materials used in lithium secondary batteries is also continuously changing, and in particular, the demand for cost reduction of positive electrode active materials is gradually increasing.
[0009] In order to meet such market demands, an object of the present invention is to provide a method for producing a positive electrode active material for a lithium secondary battery by using a precursor derived from a waste positive electrode active material during the production of the positive electrode active material.
[0010] In particular, the present invention aims to provide a method for producing a positive electrode active material for a lithium secondary battery, which can exhibit electrochemical properties and stability at a level similar to that of a positive electrode active material produced using a precursor synthesized by a conventional coprecipitation method, despite using a precursor derived from a waste positive electrode active material.
[0011] Thus, an object of the present invention is to provide a method for producing a positive electrode active material for a lithium secondary battery, which can contribute to reducing the cost of the positive electrode active material and, ultimately, the cost of lithium secondary batteries, by separating a positive electrode active material from a used lithium secondary battery that has reached the end of its life or a defective lithium secondary battery generated during the production process and utilizing the separated positive electrode active material as a raw material for producing a new positive electrode active material, which accounts for a high proportion of the cost in lithium secondary batteries.
[0012] Another object of the present invention is to provide a positive electrode comprising a positive electrode active material produced by the production method defined in the present application.
[0013] The present invention also provides a lithium secondary battery that uses the positive electrode defined herein. [Means for solving the problem]
[0014] According to one aspect of the present invention, there is provided a method for producing a cathode active material for a lithium secondary battery using a waste cathode active material, the method including: (a) mixing a waste cathode active material with a solvent to produce a slurry; (b) pulverizing the waste cathode active material from the slurry; (c) spray-drying the slurry in which the waste cathode active material is pulverized to produce a precursor; and (d) heat-treating the precursor to obtain a lithium composite oxide.
[0015] The waste positive electrode active material used in the step (a) may contain a lithium composite oxide represented by the following Chemical Formula 1 or Chemical Formula 2.
[0016] [Chemical formula 1] Li w Ni 1-x M x O 2-y X y (where: M is at least one selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu; X is selected from F, S and P; 0.5≦w≦1.5, 0≦x≦0.80, 0≦y≦2.
[0017] [Chemical formula 2] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.40, 0 <y≦0.40、0≦z≦0.40である。)
[0018] In addition, the production method according to the present invention may further include a step (e) of mixing the lithium composite oxide obtained in the step (d) with at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu and at least one selected from a lithium-containing raw material to produce a mixture, and then heat-treating the mixture.
[0019] Through the heat treatment in step (e), an oxide represented by the following Formula 3 may be formed on at least a portion of the surface of the lithium composite oxide.
[0020] [Chemical formula 3] Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦a≦10, 0 <b≦8、2≦c≦13である。)
[0021] According to another aspect of the present invention, there is provided a positive electrode active material for a lithium secondary battery having a lithium composite oxide containing at least (1) any one selected from manganese and aluminum; (2) nickel; and (3) cobalt, wherein 3 wt % or more of the total weight of the lithium composite oxide (1) any one selected from manganese and aluminum; (2) nickel; and (3) cobalt is derived from waste positive electrode active material.
[0022] The positive electrode active material may be a positive electrode active material produced by the production method according to one aspect of the present invention.
[0023] The lithium composite oxide may be represented by the following Formula 1 or Formula 2.
[0024] [Chemical formula 1] Li w Ni 1-x M x O 2-y X y (where: M is at least one selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu; X is selected from F, S and P; 0.5≦w≦1.5, 0≦x≦0.80, 0≦y≦2.
[0025] [Chemical formula 2] Li w Ni 1-(x+y+z) Co x M1 y M2z O2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.40, 0 <y≦0.40、0≦z≦0.40である。)
[0026] In addition, a coating layer containing an oxide represented by the following Chemical Formula 3 may be present on at least a portion of the surface of the lithium composite oxide.
[0027] [Chemical formula 3] Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦a≦10, 0 <b≦8、2≦c≦13である。) Effect of the Invention
[0028] According to the present invention, it is possible to produce a positive electrode active material using a precursor derived from a waste positive electrode active material, which exhibits electrochemical properties and stability at a similar level to a positive electrode active material produced using a precursor synthesized using a conventional co-precipitation method.
[0029] As a result, when producing positive electrode active materials, which account for a large proportion of costs, it is possible to separate positive electrode active materials from used lithium secondary batteries that have reached the end of their life or from defective lithium secondary batteries generated during the production process, and use the separated positive electrode active materials as raw materials for producing new positive electrode active materials, which can contribute to reducing the overall costs of positive electrode active materials and, ultimately, lithium secondary batteries.
[0030] In addition, by reusing used lithium secondary batteries that have reached the end of their life or defective lithium secondary batteries that are generated during the manufacturing process instead of disposing of them, problems such as resource waste and environmental pollution can be reduced. [Brief description of the drawings]
[0031] [Figure 1] 2 is a cross-sectional SEM image of a precursor obtained when preparing a positive electrode active material according to Example 1 of the present invention. [Diagram 2] 1 is a cross-sectional SEM image of a precursor obtained when preparing a positive electrode active material according to Example 3 of the present invention. [Diagram 3] 1 is a cross-sectional SEM image of a precursor obtained when preparing a positive electrode active material according to Comparative Example 3. [Figure 4] 1 is a cross-sectional SEM image of a precursor obtained when preparing a positive electrode active material according to Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.
[0033] Hereinafter, a method for producing a cathode active material for a lithium secondary battery using a waste cathode active material, a cathode including the cathode active material produced by the method, and a lithium secondary battery using the cathode will be described in more detail.
[0034] Method for producing positive electrode active material for lithium secondary batteries using waste positive electrode active material According to one aspect of the present invention, there is provided a method for producing a cathode active material for a lithium secondary battery using a waste cathode active material, the method including: (a) mixing a waste cathode active material with a solvent to produce a slurry; (b) pulverizing the waste cathode active material from the slurry; (c) spray-drying the slurry in which the waste cathode active material is pulverized to produce a precursor; and (d) heat-treating the precursor to obtain a lithium composite oxide.
[0035] The waste positive electrode active material used in the step (a) is used as a raw material for the positive electrode active material for a lithium secondary battery according to one embodiment of the present invention.
[0036] The waste positive electrode active material may be recovered from lithium secondary batteries (hereinafter, referred to as waste lithium secondary batteries) or positive electrodes that are in an unusable state such as those that have reached the end of their life or are defective, but is not necessarily limited thereto.
[0037] For example, a surplus positive electrode active material having a composition of NCM622 may be used to manufacture a positive electrode active material having a composition of NCM811 by the manufacturing method defined herein. In this case, even if the surplus positive electrode active material having a composition of NCM622 is not a product that has reached the end of its life or is not a defective product, it may be referred to as a waste positive electrode active material in this application for the sake of convenience.
[0038] Accordingly, in the following description, all of the various lithium composite oxides used as raw materials in step (a) of the manufacturing method defined in the present application and the cathode active materials containing the same will be referred to as waste cathode active materials.
[0039] The waste positive electrode active material used in the step (a) may contain a lithium composite oxide represented by the following Chemical Formula 1 or Chemical Formula 2.
[0040] [Chemical formula 1] Li w Ni 1-x M x O 2-y X y (where: M is at least one selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu; X is selected from F, S and P; 0.5≦w≦1.5, 0≦x≦0.80, 0≦y≦2.
[0041] [Chemical formula 2] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.40, 0 <y≦0.40、0≦z≦0.40である。)
[0042] The waste cathode active material used in the step (a) may be appropriately selected depending on the composition of the target cathode active material in the manufacturing method defined herein. However, when the elements constituting the lithium composite oxide contained in the waste cathode active material are different from the elements constituting the lithium composite oxide contained in the target cathode active material in the manufacturing method defined herein, the elements constituting the lithium composite oxide contained in the waste cathode active material may act as impurities, so it is preferable that the elements constituting the lithium composite oxide contained in the target cathode active material in the manufacturing method defined herein include at least the elements constituting the lithium composite oxide contained in the waste cathode active material.
[0043] For example, in the manufacturing method defined in the present application, when the target positive electrode active material has an NCM811 composition, the lithium composite oxide contained in the waste positive electrode active material may be a lithium composite oxide having a composition such as lithium nickel oxide (LNO), lithium cobalt oxide (LCO) and / or lithium manganese oxide (LMO), or may be a binary lithium composite oxide or a ternary lithium composite oxide such as NCM424 and / or NCM622, instead of the NCM811 composition.
[0044] In addition, the waste positive electrode active material used in the step (a) may be composed of a lithium composite oxide having the same composition, but is not necessarily limited thereto, and may be provided as a mixture containing lithium composite oxides having different compositions.
[0045] The waste positive electrode active material used in the step (a) can be recovered from the positive electrodes of waste lithium secondary batteries that are in an unusable state such as those that have reached the end of their life or are defective, etc. For example, the waste positive electrode active material present as a positive electrode active material layer in the positive electrode can be obtained by separating the positive electrode active material layer from the positive electrode (or a positive electrode current collector used in the positive electrode) and then pulverizing the separated positive electrode active material layer.
[0046] In other cases, surplus positive electrode active material that is not processed into a positive electrode or a lithium secondary battery may be used as the waste positive electrode active material.
[0047] The selected waste positive electrode active material is mixed with a solvent to prepare a slurry.
[0048] The solvent is not particularly limited as long as it can create an environment in which the subsequent process can be carried out without causing excessive chemical reaction with the waste cathode active material. For example, the solvent can be deionized water, distilled water, alcohol (ethyl alcohol, isopropyl alcohol), acetone, an aqueous acid solution, an aqueous alkali solution, or any mixture thereof.
[0049] The amount of the solvent used to prepare the slurry is not particularly limited, but it is preferable to adjust the amount of the solvent so that the viscosity of the slurry is in the range of 3,000 to 20,000 cp without decreasing the pulverization efficiency of the waste positive electrode active material in the slurry in the step (b) described below.
[0050] In addition, when preparing the slurry, at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu may be further added.
[0051] By adding the sub-raw material to the slurry before pulverizing the waste cathode active material in the slurry, the elements contained in the sub-raw material can be doped into particles formed by pulverizing the waste cathode active material in step (b) described below, or the sub-raw material and / or metal elements contained in the sub-raw material can be attached to the surfaces of the particles.
[0052] In addition, by adding the sub-raw material to the slurry before grinding the waste cathode active material, it is possible to obtain a precursor for a cathode active material without using a co-precipitation method used to synthesize a conventional precursor. In addition, when the sub-raw material is added to the slurry after grinding the waste cathode active material, an additional grinding process must be performed so that the elements contained in the sub-raw material are doped into particles formed by grinding the waste cathode active material, or the sub-raw material and / or metal elements contained in the sub-raw material are attached to the surface of the particles. Therefore, by adding the sub-raw material to the slurry before grinding the waste cathode active material, it is possible to improve process efficiency.
[0053] Here, the sub-raw material may be provided in at least one form selected from sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides.
[0054] For example, when the waste cathode active material has a composition of NCM424 and the target cathode active material in the manufacturing method defined herein has a composition of NCM811, when the slurry is manufactured, (1) a sub-raw material containing nickel (e.g., a nickel-containing hydroxide), (2) a sub-raw material containing cobalt (e.g., a cobalt-containing hydroxide), and / or (3) a sub-raw material containing manganese (e.g., a manganese-containing hydroxide) may be further added.
[0055] The amount of at least one sub-raw material further added to the slurry may vary depending on the composition of the waste cathode active material used in step (a) and the composition of the cathode active material targeted in the manufacturing method defined herein.
[0056] In addition, when preparing the slurry, a binder may be further added. The amount of the binder may vary depending on the content of the raw materials (the waste cathode active material and the sub-raw material) in the slurry and the molecular weight of the binder, but is preferably added in an amount of 1% or less based on the total weight of the raw materials (the waste cathode active material and the sub-raw material) in the slurry.
[0057] The binder acts as a binder for the waste cathode active material and the sub-raw material, and can improve the binding strength between particles. This can improve the binding strength between the sub-raw material and / or the metal elements contained in the sub-raw material and the particles formed by pulverizing the waste cathode active material in step (b) described below. In addition, by suppressing the breakage or collapse of particles in the process steps described below, a precursor and lithium composite oxide having a shape close to a sphere with high density can be formed.
[0058] Examples of the binder include lithium hydroxide, sodium hydroxide, carboxylic acid or its salt (e.g., acetic acid, acrylic acid, citric acid, ascorbic acid, formic acid, lactic acid, malic acid, malonic acid, oxalic acid, tartaric acid, polycarboxylic acid, sodium salt of polycarboxylic acid, ammonium salt of polycarboxylic acid, amine salt of polycarboxylic acid, sodium salt of carboxymethylcellulose, etc.), saccharide (starch, monosaccharide, disaccharide, polysaccharide, dextrin, cyclodextrin, maltodextrin, etc.), polymer (polyvinyl alcohol, polyvinyl butyral, polyacrylic acid, polyvinyl chloride, carboxyl Compounds that can be used include those selected from acrylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polypropylene, polyamideimide, polyimide, styrene-butadiene rubber, acrylated styrene-butadiene rubber, polyvinyl alcohol, sodium polyacrylate, copolymers of propylene and an olefin having 2 to 8 carbon atoms, copolymers of (meth)acrylic acid and an alkyl (meth)acrylic acid ester, and / or sodium dodecylbenzenesulfonate.
[0059] Next, in the step (b), the waste positive electrode active material in the slurry produced in the step (a) is pulverized.
[0060] In order to pulverize the waste positive electrode active material, a dry or wet dispersion mill such as a ball mill, a beads mill (using beads typically used for pulverizing metallic raw materials, such as Al beads, Fe beads, or Zr beads), a vibratory mill, an attritor mill, an air jet mill, a disk mill, or an air classifier mill may be used.
[0061] The waste positive electrode active material pulverized in the step (b) may have an average particle size of 0.1 μm to 5 μm.
[0062] After the pulverization in the step (b) is completed, the viscosity of the slurry is preferably in the range of 3,000 to 20,000 cp.
[0063] When the slurry has a viscosity within the above range, the condensation time during spray drying in step (c) described below can be shortened, and the amount of water lost during drying is small, making it possible to obtain a precursor with a high density.
[0064] If the viscosity of the slurry is less than 3,000 cp, not only does the condensation time during spray drying become longer, but the content of water lost during drying increases, which may reduce the density of the precursor and cause a large number of pores to form in the precursor. A precursor having low density and a large number of pores may exhibit weak particle strength. In this case, the positive electrode active material prepared using the precursor may be degraded during charging / discharging or storage of a lithium secondary battery using the positive electrode active material, and the electrochemical characteristics or stability of the lithium secondary battery may be reduced.
[0065] On the other hand, if the viscosity of the slurry exceeds 20,000 cp, the fluidity of the slurry is low in a spray dryer in which the spray drying in step (c) is performed, and therefore, not only is it difficult to achieve sufficient process efficiency, but it is also difficult to obtain a precursor having a shape close to a sphere produced through spray drying.
[0066] In addition, a binder may be added to the slurry before the slurry is spray-dried in step (c), where the binder may be the same as the binder used in step (a) described above.
[0067] The amount of the binder added may vary depending on the content of the raw materials (the waste cathode active material and the sub-raw material) in the slurry and the molecular weight of the binder, but is preferably added in an amount of 1% or less based on the total weight of the raw materials (the waste cathode active material and the sub-raw material) in the slurry. If the binder has already been added in step (a), it is preferable that the sum of the amount of the binder added in step (a) and the amount of the binder added before step (c) be 1% or less based on the total weight of the raw materials (the waste cathode active material and the sub-raw material) in the slurry.
[0068] Before spray drying the slurry in the step (c), the temperature of the slurry is preferably adjusted to within a range of 15 to 70° C. In this case, the temperature of the slurry before spray drying means the temperature of the slurry before the slurry is introduced into a spray dryer in which the spray drying in the step (c) is performed.
[0069] If the temperature of the slurry is less than 15° C., the temperature difference between the temperature of the environment in which the spray drying is performed in step (c) is large, and therefore the thermal shock applied to the particles (pulverized waste cathode active material) of the slurry may be excessively large, which may result in the collapse of the particles (pulverized waste cathode active material) of the slurry.
[0070] On the other hand, if the temperature of the slurry exceeds 70° C., it is difficult to accurately control the viscosity of the slurry due to evaporation of the solvent in the slurry.
[0071] As described above, the slurry in which the waste positive electrode active material is pulverized may be spray-dried in the step (c) to obtain a precursor.
[0072] The step (c) may be performed in a spray dryer. The spray dryer is not particularly limited as long as it is a spray drying device that can spray-dry the slurry containing the pulverized waste cathode active material to produce a dried precursor having a nearly spherical shape. Examples of the spray dryer include an ultrasonic atomizer, a one-fluid jet nozzle sprayer, a two-fluid jet nozzle sprayer, an ultrasonic nozzle sprayer, a filter expansion droplet generator (FEAG), and a disk-type droplet generator.
[0073] The spray dryer in which the spray drying in step (c) is performed may include a spray nozzle and a drying chamber, and the slurry is atomized into droplets of a predetermined size through the spray nozzle and sprayed into the drying chamber in the presence of a relatively high temperature gas flow.
[0074] The raw materials (the waste positive electrode active material and the sub-raw material) in the droplets sprayed into the drying chamber are synthesized as dried precursors having a shape close to spheres under the temperature environment in the drying chamber.
[0075] In order to convert the source material in the droplets into a precursor, the temperature in the drying chamber is preferably adjusted to within a range of 50 to 500°C.
[0076] The viscosity of the slurry to be spray-dried in step (c) is 3,000 to 20,000 cp, and the flow rate of the compressed air used to spray-dry the relatively high-viscosity slurry through the spray nozzle is preferably 40 L / min or more. If the flow rate of the compressed air is less than 40 L / min, the spray nozzle may be clogged with the relatively high-viscosity slurry, reducing the efficiency of the spray-drying process.
[0077] In addition, since the slurry has a viscosity within the above-mentioned range, the condensation time during spray drying can be shortened, and the amount of water lost during drying is small, making it possible to obtain a precursor with high density.
[0078] If the viscosity of the slurry in step (c) is less than 3,000 cp, not only will the condensation time during spray drying be longer, but the amount of water lost during drying will increase, which may result in a decrease in the density of the precursor and a large number of pores being formed in the precursor. A precursor having low density and a large number of pores may exhibit weak particle strength. In this case, the positive electrode active material prepared using the precursor may be degraded during charging / discharging or storage of a lithium secondary battery using the positive electrode active material, which may result in a decrease in electrochemical properties or stability of the lithium secondary battery.
[0079] On the other hand, when the viscosity of the slurry exceeds 20,000 cp, the fluidity of the slurry in the spray dryer is low, so that not only is it difficult to achieve sufficient process efficiency, but it is also difficult to obtain a precursor having a shape close to a sphere produced through spray drying.
[0080] In addition, specific conditions for the spray drying carried out in the step (c) can be referred to the production examples described below.
[0081] The precursor produced in the step (c) has an average particle size of 0.1 μm to 20 μm, and the 50% cumulative volume particle size D 50 and 10% cumulative volumetric grain size D 10 Percentage of D 50 / D 10 is preferably in the range of 1.92 to 6.24.
[0082] D 50 / D 10 In order to improve the electrode density, it is preferable that the D is at least 1.92 or more. 50 / D 10 If the particle size distribution of the precursor is too broad, it is difficult to obtain a lithium composite oxide having a uniform particle diameter through a subsequent process.
[0083] In addition, when a cathode active material is prepared using a precursor derived from a waste cathode active material by the preparation method defined in the present application instead of using a precursor synthesized by a coprecipitation method, the density of the lithium composite oxide contained in the cathode active material may decrease, or a large amount of pores may be formed in the lithium composite oxide, resulting in weak particle strength. In this case, the cathode active material may break down during charging / discharging or storage of a lithium secondary battery using the cathode active material, resulting in a decrease in electrochemical characteristics or stability of the lithium secondary battery.
[0084] However, in the case of the cathode active material prepared by the method according to the present invention, the particle strength of the lithium composite oxide can be improved by increasing the density of the precursor derived from the waste cathode active material and reducing the formation of pores at the same time. The particle strength of the cathode active material prepared using the precursor derived from the waste cathode active material or the precursor derived from the waste cathode active material can be confirmed by measuring the particle size distribution that changes through an artificial physical treatment of the precursor or the cathode active material.
[0085] For example, the D of the precursor produced in step (c) was measured after subjecting the precursor to ultrasonic treatment at a frequency of 40 kHz for 60 seconds. 50 / D 10 The rate of change may be 43% or less.
[0086] After ultrasonic treatment of the precursor under the above conditions, the D 50 / D 10 If the rate of change exceeds 43%, the particle strength of the precursor is insufficient, and the stability of the positive electrode active material prepared using the precursor may be reduced.
[0087] Next, a step (d) is carried out in which the precursor produced in the step (c) is heat-treated to obtain a lithium composite oxide.
[0088] In one embodiment, before the heat treatment of the precursor produced in step (c) in step (d), at least one selected from at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu and a lithium-containing raw material may be further added. The sub-raw material may be provided in at least one form selected from sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides.
[0089] The amount of the sub-raw material added in step (d) may vary depending on the composition of the waste cathode active material and the composition of the cathode active material targeted in the manufacturing method defined herein.
[0090] Accordingly, when the mixture of the precursor and the sub-raw material is heat-treated in the step (d), the lithium composite oxide may be doped with the element contained in the sub-raw material, or at least a portion of the surface of the lithium composite oxide may be coated with an oxide represented by Chemical Formula 3 described below.
[0091] The elements contained in the sub-raw material are doped into the lithium composite oxide, thereby improving the electrochemical properties and stability of the lithium composite oxide.
[0092] The lithium-containing raw material may be lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, or the like.
[0093] The content of the lithium-containing raw material to be added in the step (d) is preferably such that the ratio Li / Metal of the number of lithium atoms Li to the total number of atoms Metal of metal elements other than lithium among the raw materials (precursor, sub-raw material and lithium-containing raw material) in the step (d) is in the range of 1.5 or less.
[0094] If the lithium-containing raw material is further added when preparing a mixture in the step (e) described below, it is preferable that the content of the lithium compound added in the step (d) is such that the ratio Li / Metal of the number of lithium atoms Li to the total number of atoms Metal of metal elements other than lithium in the raw material is 1.0 or less, and the content of the lithium compound added in the step (e) is such that the ratio Li / Metal of the number of lithium atoms Li to the total number of atoms Metal of metal elements other than lithium in the raw material is 1.5 or less.
[0095] The lithium-containing raw material may react with the precursor to induce lithiation of the precursor and may also act as a binder for the precursor and the sub-raw material to improve interparticle binding strength.
[0096] The heat treatment temperature in step (d) may be 300 to 1,000° C., and the heat treatment temperature in step (d) may vary depending on the composition of the waste cathode active material and the composition of the target cathode active material in the manufacturing method defined herein.
[0097] More specifically, the heat treatment in step (d) may be performed in a calcination furnace under an O2 atmosphere at a temperature of 300 to 1,000°C at a rate of 2 to 5°C per minute for 5 to 12 hours. If the heat treatment temperature in step (d) is less than 300°C, the calcination of the precursor may be insufficient, resulting in insufficient crystal growth of the lithium composite oxide. On the other hand, if the heat treatment temperature in step (c) exceeds 1,000°C, the lithium composite oxide may be thermally decomposed, resulting in a decrease in particle strength or particle collapse.
[0098] The lithium composite oxide obtained in the step (d) may include primary particles and secondary particles formed by aggregation of the primary particles. Similarly, the lithium composite oxide is represented by Chemical Formula 1 or Chemical Formula 2, but does not necessarily have to have the same composition as the waste cathode active material used as a raw material.
[0099] In addition, a step (e) of mixing at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu and at least one selected from a lithium-containing raw material with the lithium composite oxide obtained in the step (d) to prepare a mixture may be further performed.
[0100] The amount of the sub-raw material added in step (e) may vary depending on the composition of the waste cathode active material and the composition of the cathode active material targeted in the manufacturing method defined herein.
[0101] The sub-raw material may be provided in at least one form selected from sulfates, carbonates, nitrates, acetates, chlorides, hydroxides and oxides.
[0102] In the step (e), when the mixture of the lithium composite oxide and the sub-raw material is heat-treated, at least a portion of the surface of the lithium composite oxide may be coated with an oxide represented by the following Chemical Formula 3:
[0103] [Chemical formula 3] Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦a≦10, 0 <b≦8、2≦c≦13である。)
[0104] The oxide represented by Chemical Formula 3 may be present on at least a portion of the surface of the lithium composite oxide, and the region of the surface of the lithium composite oxide where the oxide represented by Chemical Formula 3 is present may be defined as a coating layer.
[0105] In addition, when the lithium composite oxide includes primary particles and secondary particles formed by agglomeration of the primary particles, the oxide represented by Chemical Formula 2 may be present on at least a portion of the surface of the primary particles (e.g., interfaces between the primary particles) and / or the secondary particles formed by agglomeration of the primary particles. The coating layer may be present as a layer that continuously or discontinuously coats the surfaces of the primary particles and / or the secondary particles formed by agglomeration of the primary particles. When the coating layer is present discontinuously, it may be present in the form of islands.
[0106] In some cases, the oxide may be present not only at the interfaces between the primary particles and at least a portion of the surfaces of the secondary particles, but also in internal voids formed inside the secondary particles.
[0107] In this case, the coating layer may be in the form of a solid solution that does not form a boundary with the primary particles and / or the secondary particles formed by agglomeration of the primary particles, but is not limited thereto.
[0108] The coating layer may contribute to improving the stability of the lithium composite oxide by removing residual lithium by-products present on the surface of the lithium composite oxide and improving the electrochemical properties of the lithium composite oxide.
[0109] Also, as described in the step (d), when preparing the mixture in the step (e), the lithium-containing raw material may be further added.
[0110] The lithium-containing raw material further added in the step (e) is a lithium compound capable of inducing further lithiation of the lithium composite oxide during the heat treatment in the step (e). Examples of the lithium compound include lithium hydroxide, lithium carbonate, lithium nitrate, and lithium acetate.
[0111] The lithium compound further added in the step (e) is preferably mixed so that the ratio Li / Metal of the number of lithium atoms Li to the total number of atoms Metal of metal elements other than lithium in the final product lithium composite oxide is in the range of 1.5 or less.
[0112] The heat treatment temperature in the step (e) for forming the coating layer on the surface of the lithium composite oxide may be 300 to 1,000°C. More specifically, the heat treatment in the step (e) may be performed in a sintering furnace under an O2 atmosphere, with the temperature increased from 300 to 1,000°C at a rate of 2 to 5°C per minute for 5 to 12 hours. If the heat treatment temperature in the step (e) is less than 300°C, the crystal growth of the oxide constituting the coating layer on the surface of the lithium composite oxide is insufficient. On the other hand, if the heat treatment temperature in the step (e) exceeds 1,000°C, thermal decomposition of the lithium composite oxide and / or the oxide may occur.
[0113] In addition, before carrying out the step (e), the lithium composite oxide obtained in the step (d) may be subjected to a disintegration, distribution, iron removal and / or water washing step.
[0114] In particular, before carrying out the step (e), a water washing step can be optionally carried out on the lithium composite oxide obtained in the step (d).
[0115] Impurities remaining in the lithium composite oxide (e.g., including residual lithium by-products and / or unreacted sub-raw material) can be removed by reacting the lithium composite oxide obtained in the step (d) with a washing solution, thereby inducing an intentional reaction between the lithium composite oxide and the sub-raw material for forming a coating layer on the surface of the lithium composite oxide in the step (e).
[0116] positive electrode active material According to another aspect of the present invention, there is provided a cathode active material produced by the above-described production method, i.e., using waste cathode active material.
[0117] The positive electrode active material is provided as an aggregate containing primary particles made of a lithium composite oxide capable of lithium intercalation / deintercalation and secondary particles in which a plurality of the primary particles are aggregated together.
[0118] Here, the primary particle refers to one crystal grain or crystallite, and the secondary particle refers to an aggregate formed by agglomeration of a plurality of primary particles. The primary particles may have a rod shape, an elliptical shape, and / or an irregular shape. A gap and / or a grain boundary may exist between the primary particles constituting the secondary particles. In another embodiment, the positive electrode active material may include a lithium composite oxide that exists in a single crystal form having an average particle size of 0.1 μm or more.
[0119] The primary particles may be separated from adjacent primary particles within the secondary particle to form internal voids. Also, the primary particles may not contact adjacent primary particles to form grain boundaries, but may contact internal voids to form a surface present within the secondary particle. The surface of the primary particles present at the outermost surface of the secondary particle, exposed to the outside air, forms the surface of the secondary particle.
[0120] Here, the average particle size of the primary particles (here, the average particle size of the primary particles may be the average major axis length of the primary particles) is within a range of 0.1 μm to 5 μm, thereby making it possible to realize optimal density of a cathode manufactured using the cathode active material according to various embodiments of the present invention. In addition, the cathode active material manufactured using the waste cathode active material according to the manufacturing method defined in the present application has improved particle strength, so that even if the average particle size of the primary particles is within a range of 0.1 μm to 5 μm, the possibility of particle breakage occurring is low.
[0121] The average particle size of the secondary particles formed by agglomeration of a plurality of the primary particles may vary depending on the number of agglomerated primary particles, but may generally be 3 μm to 20 μm.
[0122] The lithium composite oxide may be represented by the following Formula 1 or Formula 2.
[0123] [Chemical formula 1] Li w Ni 1-x M x O 2-y X y (where: M is at least one selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu; X is selected from F, S and P; 0.5≦w≦1.5, 0≦x≦0.80, 0≦y≦2.
[0124] [Chemical formula 2] Li w Ni 1-(x+y+z) Co x M1 y M2 z O2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.40, 0 <y≦0.40、0≦z≦0.40である。)
[0125] The composition of the lithium composite oxide may vary depending on the composition of the waste positive electrode active material as a raw material used in the preparation method defined herein and the type and composition of the sub-raw material further used therein.
[0126] In particular, when the positive electrode active material according to the present invention has a lithium composite oxide containing at least (1) any one selected from manganese and aluminum; (2) nickel; and (3) cobalt, 3 wt % or more, preferably 5 wt % or more, of the lithium composite oxide may be derived from waste positive electrode active material, based on the total weight of (1) any one selected from manganese and aluminum; (2) nickel; and (3) cobalt.
[0127] The cathode active material according to the present invention is a cathode active material manufactured using a waste cathode active material, and the content of the components derived from the waste cathode active material in the cathode active material may vary depending on the composition of the waste cathode active material or the composition of the target cathode active material, but the more the content of the components derived from the waste cathode active material in the final cathode active material increases, the more the cost of the cathode active material and, in turn, the lithium secondary battery can be reduced. However, if the content of the components derived from the waste cathode active material in the cathode active material is excessively high, the electrochemical properties or stability of the cathode active material may be reduced, and therefore, the total content of the components derived from the waste cathode active material in the cathode active material is preferably 70 wt% or less.
[0128] In addition, the 50% cumulative volume particle size D of the positive electrode active material produced using the waste positive electrode active material by the production method defined in the present application is 50 and 10% cumulative volumetric grain size D 10 Percentage of D 50 / D 10 is preferably 2.0 to 7.0 in order to improve the density of an electrode manufactured using the positive electrode active material.
[0129] In addition, when a cathode active material is prepared using a precursor derived from a waste cathode active material by the preparation method defined in the present application instead of using a precursor synthesized by a coprecipitation method, the density of the lithium composite oxide contained in the cathode active material may decrease, or a large amount of pores may be formed in the lithium composite oxide, resulting in weak particle strength. In this case, the cathode active material may be degraded during charging / discharging or storage of a lithium secondary battery using the cathode active material, resulting in poor electrochemical properties or stability of the lithium secondary battery.
[0130] However, in the case of a cathode active material prepared by the method defined herein, the particle strength of the lithium composite oxide can be improved by improving the density of the precursor derived from the waste cathode active material and reducing the formation of pores at the same time. The particle strength of the cathode active material prepared using the precursor derived from the waste cathode active material can be confirmed by measuring the particle size distribution that changes through an artificial physical treatment of the precursor or the cathode active material.
[0131] For example, the D of the lithium composite oxide measured after subjecting the positive electrode active material to ultrasonic treatment at a frequency of 40 kHz for 60 seconds 50 / D 10 The rate of change may be 10% or less.
[0132] After ultrasonic treatment of the positive electrode active material under the above conditions, the lithium composite oxide D 50 / D 10If the rate of change exceeds 10%, the particle strength of the positive electrode active material is insufficient, and the stability of a lithium secondary battery using the positive electrode active material may be reduced.
[0133] In addition, the positive electrode active material may include a coating layer that covers at least a portion of the surfaces of the primary particles (e.g., interfaces between the primary particles) and / or secondary particles formed by aggregation of the primary particles.
[0134] For example, the coating layer may be present so as to cover at least a portion of the exposed surface of the primary particles, particularly, the coating layer may be present so as to cover at least a portion of the exposed surface of the primary particles present at the outermost portion of the secondary particles.
[0135] Thus, the coating layer may exist as a layer that coats the surfaces of the primary particles and / or the secondary particles formed by agglomeration of the primary particles continuously or discontinuously. When the coating layer exists discontinuously, it may exist in the form of islands.
[0136] In some cases, the oxide may be present not only at the interfaces between the primary particles and at least a portion of the surfaces of the secondary particles, but also in internal voids formed inside the secondary particles.
[0137] The coating layer thus present can contribute to improving the electrochemical properties and stability of the positive electrode active material.
[0138] In this case, the coating layer may be in the form of a solid solution that does not form a boundary with the primary particles and / or the secondary particles formed by aggregation of the primary particles, but is not limited thereto.
[0139] In addition, the coating layer may contain at least one oxide represented by the following chemical formula 2. That is, the coating layer can be defined as a region in which an oxide represented by the following chemical formula 3 is present.
[0140] [Chemical formula 3] Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦a≦10, 0 <b≦8、2≦c≦13である。)
[0141] The oxide represented by the formula 3 is an oxide of lithium and an element represented by A, or an oxide of A. The oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a Co b O c , Li a Al b O c , Co b O c , Al b O c , W b O c , Zr b O c or Ti b O c However, the above-mentioned examples are merely given for the sake of convenience to facilitate understanding, and the oxide defined in the present application is not limited to the above-mentioned examples.
[0142] In another embodiment, the oxide represented by Chemical Formula 3 may be an oxide in which lithium and at least two elements represented by A are combined, or may further include an oxide in which lithium and at least two elements represented by A are combined. The oxide in which lithium and at least two elements represented by A are combined may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c It may be, but is not limited to, the above.
[0143] As described above, the positive electrode active material according to the present embodiment has high structural stability by including a coating layer that covers at least a portion of the surface of the primary particles (e.g., interfaces between the primary particles) and / or secondary particles formed by agglomeration of the primary particles. In addition, the positive electrode active material is used as a positive electrode active material for a lithium secondary battery, thereby improving the life and capacity characteristics.
[0144] In addition, the coating layer reduces residual lithium in the lithium composite oxide and acts as a diffusion path for lithium ions, thereby improving the efficiency characteristics of the lithium secondary battery.
[0145] In addition, the oxide may exhibit a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, whereby the concentration of the oxide may decrease from the outermost surface of the secondary particle toward the center portion of the secondary particle.
[0146] As described above, the oxide exhibits a concentration gradient that decreases from the surface portion of the secondary particle toward the center portion of the secondary particle, thereby effectively reducing the residual lithium present on the surface of the positive electrode active material, and thus preventing side reactions due to unreacted residual lithium. In addition, the oxide can prevent the crystallinity of the surface inner region of the positive electrode active material from decreasing. In addition, the oxide can prevent the overall structure of the positive electrode active material from collapsing during an electrochemical reaction.
[0147] Lithium secondary battery According to yet another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a layer of the above-described positive electrode active material formed on the positive electrode current collector, wherein the positive electrode active material layer may include the positive electrode active material manufactured by the manufacturing method according to the various embodiments of the present invention as the positive electrode active material.
[0148] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0149] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.
[0150] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.
[0151] The conductive material is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0152] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0153] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.
[0154] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.
[0155] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.
[0156] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0157] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. The lithium secondary battery may be provided as an anode-free lithium secondary battery. Here, since the positive electrode is as described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described in detail below. Also, it should be understood that the description related to the negative electrode described below will be given on the assumption that the lithium secondary battery includes a negative electrode.
[0158] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0159] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0160] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0161] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.
[0162] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0163] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.
[0164] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0165] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.
[0166] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0167] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0168] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.
[0169] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0170] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0171] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.
[0172] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.
[0173] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.
[0174] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0175] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.
[0176] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.
[0177] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0178] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.
[0179] Production Example 1: Production of positive electrode active material using waste positive electrode active material (1) Example 1 Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, a used lithium secondary battery was used to recover a used cathode active material having an average particle size of 15 μm, and the composition of the recovered used cathode active material was confirmed by ICP-OES.
[0180] Beads of 0.6 mm and 0.3 mm in size were placed in a bead mill (Netch, LabStar Mini) so that they filled 70% of the internal space of the bead mill, and then deionized water (DIW) was added in a weight ratio of 1:1 to the beads and circulated.
[0181] The waste positive electrode active material, nickel hydroxide, and cobalt hydroxide were weighed and charged into a bead mill so that the molar ratio of Ni, Co, and Mn in the target positive electrode active material was 80:10:10 relative to 0.2 kg of the waste positive electrode active material, and then stirred to produce a slurry. Next, the waste positive electrode active material in the slurry was pulverized in the bead mill so that the average particle size of the waste positive electrode active material was 0.5 μm or less. After the pulverization was completed, the viscosity of the slurry was measured to be 5,000 cp and the temperature of the slurry was measured to be 25° C.
[0182] The prepared slurry was put into a raw material storage container attached to a spray dryer (Toshin Giken, DJE003R) and stirred at 200 rpm to prevent the slurry from settling and separating. The stirring speed of the slurry was adjusted to decrease as the amount of the slurry in the raw material storage container decreased.
[0183] The slurry was transferred to a spray-drying chamber by a tube-type feeding pump at a transfer rate of 1 kg / h. The atomizer used for spray-drying was a two-fluid injection nozzle, and the inlet temperature was maintained at 235°C and the outlet temperature was maintained at 100°C or higher.
[0184] In the drying chamber, the temperature was kept constant at 235° C. to rapidly remove moisture, and the slurry sprayed from the spray nozzle was atomized in the form of droplets to produce a spherical ultrafine powder form (precursor).
[0185] In the spray drying process, the air is drawn in and heated, and the hot air is brought into contact with the droplets sprayed in a co-current flow during the drying process, and the evaporated water vapor is discharged into the atmosphere or removed by installing a vapor trap to produce the precursor. The cross-sectional SEM image of the produced precursor is shown in Figure 1.
[0186] The prepared precursor was then charged into a gravity-free mixer, lithium hydroxide was added, and the mixture was stirred for 1 hour to prepare a mixture. The amount of lithium hydroxide added was adjusted so that the ratio Li / Metal of the total number of atoms of Li added as lithium hydroxide and Li in the precursor to the total number of atoms of metal elements other than Li in the precursor, Metal, was 1.05.
[0187] Next, the mixture was heat-treated in a sintering furnace in an O2 atmosphere for 12 hours at a temperature of 680°C at a rate of 2°C per minute to obtain a lithium composite oxide (positive electrode active material).
[0188] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 O2(NCM811). In addition, the weight of the waste cathode active material used as a raw material was calculated to be 30.9 wt% based on the total weight of the finally obtained cathode active material, as shown in Table 1 below.
[0189] [Table 1]
[0190] (2) Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 8,000 cp before spray drying.
[0191] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0192] (3) Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 15,000 cp before spray drying.
[0193] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0194] A cross-sectional SEM image of the precursor obtained when preparing the positive active material according to Example 3 is shown in FIG.
[0195] (4) Example 4 A positive electrode active material was produced in the same manner as in Example 1, except that ZrO2 was weighed and mixed with the precursor to give a concentration of 0.1 mol % before the precursor was heat-treated.
[0196] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.79 Co 0.09 Mn 0.09 Zr 0.01 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0197] (5) Example 5 The precursor was heat-treated to obtain a lithium composite oxide, and then TiO2 was weighed and mixed with the lithium composite oxide to give a content of 0.3 mol %. A positive electrode active material was produced in the same manner as in Example 1.
[0198] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.79 Co 0.09 Mn0.09 Ti 0.02 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0199] (6) Examples 6 to 8 The raw material is Li[Ni 0.4 Co 0.2 Mn 0.4 ]O2(NCM424), Li[Ni 0.5 Co 0.2 Mn 0.3 ]O2(NCM523) and Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2(NCM622) and the waste cathode active material were used to manufacture cathode active materials in the same manner as in Example 1. In addition, in the case of Example 6, the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 3,000 cp before spray drying, and in the case of Example 8, the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 20,000 cp before spray drying.
[0200] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was Li 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste cathode active material used as a raw material relative to the total weight of the finally obtained cathode active material was calculated as shown in Table 2 below.
[0201] [Table 2]
[0202] (7) Examples 9 to 12 The raw material is Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2(NCM333), Li[Ni 0.4 Co 0.2 Mn0.4 ]O2(NCM424), Li[Ni 0.5 Co 0.2 Mn 0.3 ]O2(NCM523) and Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2(NCM622) and the molar ratio of Ni, Co and Mn in the target positive electrode active material was 88:10:2, and the positive electrode active materials were produced in the same manner as in Example 1.
[0203] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was Li 1.05 Ni 0.88 Co 0.1 Mn 0.02 The weight of the waste cathode active material used as a raw material relative to the total weight of the finally obtained cathode active material was calculated as shown in Table 3 below.
[0204] [Table 3]
[0205] (8) Comparative Example 1 The [Ni 0.8 Co 0.1 Mn 0.1 ]OH2 precursor was used to prepare the positive electrode active material.
[0206] As a result of ICP-OES analysis of the prepared positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 It was confirmed to be O2.
[0207] (9) Comparative Example 2 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 500 cp before spray drying.
[0208] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0209] (10) Comparative Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that the content of pure water in the slurry was adjusted so that the viscosity of the slurry was 2,000 cp before spray drying.
[0210] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1. A cross-sectional SEM image of the precursor obtained when preparing the positive electrode active material according to Comparative Example 3 is shown in FIG. 3.
[0211] (10) Comparative Example 4 A positive electrode active material was produced in the same manner as in Example 1, except that the waste positive electrode active material was pulverized in a bead mill so that the average particle size was 0.5 μm or less, and nickel hydroxide and cobalt hydroxide were weighed and added to the slurry.
[0212] As a result of ICP-OES analysis of the obtained positive electrode active material, the composition of the positive electrode active material was 1.05 Ni 0.8 Co 0.1 Mn 0.1 The weight of the waste positive electrode active material relative to the total weight of the positive electrode active material obtained was the same as in Example 1.
[0213] A cross-sectional SEM image of the precursor obtained when preparing the positive active material according to Comparative Example 4 is shown in FIG.
[0214] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 92 wt% of the positive electrode active material prepared in Preparation Example 1, 4 wt% of artificial graphite, and 4 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0215] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte solution of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.
[0216] Experimental Example 1: Evaluation of particle characteristics of positive electrode active material 0.1 g each of the precursor and lithium composite oxide obtained when producing the positive electrode active material in Production Example 1 was added to 50 ml of sodium hexametaphosphate aqueous solution and dispersed to obtain a dispersion. Next, the average particle size and particle size distribution of the precursor and lithium composite oxide in the dispersion were measured using a laser diffraction scattering particle size distribution measurement device (Cilas PSA 1060), and a volume-based cumulative particle size distribution curve was obtained.
[0217] Next, the dispersion was subjected to ultrasonic treatment at a frequency of 40 kHz for 60 seconds using an ultrasonic treatment unit included in the particle size distribution measuring device, and then subjected to ultrasonic treatment at a frequency of 40 kHz for 60 seconds using an ultrasonic treatment unit included in the particle size distribution measuring device. 50 / D 10 The rate of change was measured.
[0218] In the obtained cumulative particle size distribution curve, the volume particle size at 10% accumulation is called the 10% cumulative volume particle size D 10 , the volumetric grain size at 50% accumulation is 50% cumulative volumetric grain size D 50 , the volumetric grain size at 90% accumulation is 90% cumulative volumetric grain size D 90 It was decided.
[0219] D50 / D 10 The rate of change was calculated as follows:
[0220] D 50 / D 10 Change rate (%) = (|D after ultrasonic treatment) 50 / D 10 -D before sonication 50 / D 10 | / D before sonication 50 / D 10 ) x 100
[0221] The results of measuring the particle size distribution of the precursor are shown in Tables 4 and 5 below, and the results of measuring the particle size distribution of the lithium composite oxide are shown in Tables 6 and 7 below.
[0222] [Table 4]
[0223] [Table 5]
[0224] Referring to the results in Tables 4 and 5, the [Ni 0.8 Co 0.1 Mn 0.1 When comparing the positive electrode active materials prepared using the waste positive electrode active materials except for the positive electrode active material precursor prepared using the ]OH precursor, it can be seen that the change in particle size distribution after ultrasonic treatment of the positive electrode active material precursors according to Examples 1 to 12 is smaller than that of the positive electrode active material precursors according to Comparative Examples 2 to 4.
[0225] [Table 6]
[0226] [Table 7]
[0227] Referring to the results in Tables 6 and 7, the [Ni 0.8 Co 0.1 Mn 0.1 When comparing the cathode active materials prepared using waste cathode active materials with the cathode active material prepared in Comparative Example 1, which is a cathode active material prepared using an ]OH precursor, it can be seen that the change in particle size distribution after ultrasonic treatment for the cathode active materials (lithium composite oxides) according to Examples 1 to 12 is smaller than that for the cathode active materials (lithium composite oxides) according to Comparative Examples 2 to 4.
[0228] In particular, the positive electrode active materials (lithium composite oxides) according to Examples 1 to 12 show a change in particle size distribution at a level similar to that of Comparative Example 1, and are therefore expected to have sufficient strength and stability as positive electrode active materials for lithium secondary batteries.
[0229] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries A charge-discharge experiment was carried out on the lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, voltage range of 3.0V to 4.3V, and discharge rate of 0.1C to measure the charge and discharge capacities. In addition, the same lithium secondary battery was charged and discharged 100 times at 25°C and 0.1C / 0.1C within a driving voltage range of 3.0V to 4.3V, and then the ratio of the discharge capacity at the 100th cycle to the initial capacity (cycle capacity retention) was measured.
[0230] The measurement results are shown in Table 8 below.
[0231] [Table 8]
[0232] Referring to the results in Table 8, [Ni 0.8 Co 0.1 Mn0.1 When compared with Comparative Example 1, which is a cathode active material prepared using an ]OH precursor, it can be seen that the lithium secondary batteries using the cathode active materials (lithium composite oxides) according to Examples 1 to 12 prepared using the waste cathode active material also exhibit similar levels of electrochemical characteristics.
[0233] Experimental Example 3. Evaluation of the stability of positive electrode active materials and lithium secondary batteries (1) Evaluation of thermal stability of positive electrode active material In order to evaluate the thermal stability of the positive electrode active material prepared in Preparation Example 1, the weight loss was measured at a heating rate of 10°C / min from 25°C to 350°C under Ar atmosphere at normal pressure using a thermogravimetric analyzer (TA Instruments, Q20). The on-set temperature at which the weight loss (thermal decomposition) peak appeared for each positive electrode active material is shown in Table 9 below.
[0234] [Table 9]
[0235] Referring to the results in Table 9, it can be seen that the on-set temperatures at which the weight loss (thermal decomposition) peak appears in the cathode active materials according to Examples 1 to 12 prepared using the waste cathode active materials are similar to or even higher than those of the cathode active materials according to Comparative Examples 1 to 4. This confirms that the thermal stability of the cathode active materials according to Examples 1 to 12 is sufficiently ensured.
[0236] (2) Measurement of gas generation rate of lithium secondary batteries The lithium secondary battery prepared according to Preparation Example 2 was charged to 4.25 V at a constant current of 0.2 C, and then stored at 60° C. for 14 days to measure the volume change of the lithium secondary battery due to gas generation in the lithium secondary battery. The volume change measurement results are shown in Table 10 below.
[0237] [Table 10]
[0238] Referring to the results in Table 10, [Ni 0.8 Co 0.1 Mn 0.1 When comparing the cathode active materials prepared using waste cathode active materials with the cathode active material prepared in Comparative Example 1 using the cathode active material prepared using the ]OH precursor, it can be seen that the volume change of the lithium secondary batteries prepared using the cathode active materials (lithium composite oxides) according to Examples 1 to 12 is smaller than that of the lithium secondary batteries prepared using the cathode active materials (lithium composite oxides) according to Comparative Examples 2 to 4.
[0239] In particular, the positive electrode active materials (lithium composite oxides) according to Examples 1 to 12 exhibit a volume change at a similar level to that of Comparative Example 1, and are therefore expected to ensure sufficient stability as positive electrode active materials for lithium secondary batteries.
[0240] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.
Claims
1. Step (a) mixing the waste positive electrode active material with a solvent to produce a slurry; step (b) pulverizing the waste positive electrode active material from the slurry; Step (c) spray-drying the slurry in which the waste positive electrode active material is pulverized to produce a precursor; and Step (d) heat-treating the precursor to obtain a lithium composite oxide; Including, The 50% cumulative volumetric particle size D of the precursor produced in step (c) 50 and 10% cumulative volumetric grain size D 10 Proportion D 50 / D 10 The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material, wherein the average molecular weight of the positive electrode active material is 1.92 to 6.
24.
2. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, wherein the waste positive electrode active material used in the step (a) comprises a lithium composite oxide represented by the following Chemical Formula 1: [Chemical formula 1] Li w Ni 1-x M x O 2-y X y (where: M is at least one selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu; X is selected from F, S and P; 0.5≦w≦1.5, 0≦x≦0.80, 0≦y≦2.)
3. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, wherein the waste positive electrode active material used in the step (a) comprises a lithium composite oxide represented by the following chemical formula 2: [Chemical formula 2] Li w Ni 1-(x+y+z) Co x M1 y M2 z O 2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from Mn, B, Ba, Ce, Hf, Ta, Cr, F, Mg, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu; M1 and M2 are different elements, 0.5≦w≦1.5, 0≦x≦0.40, 0<y≦0.40, 0≦z≦0.40.)
4. 4. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 2 or 3, wherein in the step (a), at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, Sr, Ge, Nd, Gd, and Cu is further added to the slurry.
5. 5. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 4, wherein the sub-raw material is provided in at least one form selected from the group consisting of sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides.
6. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 1 , wherein a binder is further added to the slurry in the step (a).
7. 2. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, wherein the average particle size of the waste positive electrode active material pulverized in the step (b) is 0.1 μm to 5 μm.
8. 2. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 1, further comprising adding a binder to the slurry before spray-drying the slurry in the step (c).
9. 2. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 1, wherein the viscosity of the slurry is adjusted to a range of 3,000 to 20,000 cp before the slurry is spray-dried in the step (c).
10. 2. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 1, wherein the temperature of the slurry is adjusted to a range of 15 to 70° C. before the slurry is spray-dried in the step (c).
11. D after the precursor prepared in step (c) was ultrasonically treated at a frequency of 40 kHz for 60 seconds 50 / D 10 2. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, wherein the rate of change of is 43% or less.
12. 2. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, further comprising: adding at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu, and at least one selected from a lithium-containing raw material, before the precursor is heat-treated in step (d).
13. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 12, wherein the sub-raw material is provided in at least one form selected from the group consisting of sulfates, carbonates, nitrates, acetates, chlorides, hydroxides, and oxides.
14. 2. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 1, wherein the lithium composite oxide obtained in the step (d) contains primary particles and secondary particles formed by aggregation of the primary particles.
15. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 14, wherein the average particle size of the primary particles is 0.1 μm to 5 μm.
16. 2. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 1, further comprising a step (e) of mixing at least one sub-raw material containing an element selected from Mn, Co, Al, B, Ba, Ce, Hf, Ta, Cr, F, Mg, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu and at least one selected from a lithium-containing raw material material with the lithium composite oxide obtained in the step (d) to produce a mixture, and then heat-treating the mixture.
17. The method for producing a positive electrode active material for a lithium secondary battery using a waste positive electrode active material according to claim 16, wherein the sub-raw material is provided in at least one form selected from sulfates, carbonates, nitrates, acetates, chlorides, hydrates, and oxides.
18. 17. The method for producing a positive electrode active material for a lithium secondary battery using the waste positive electrode active material according to claim 16, wherein an oxide represented by the following Chemical Formula 3 is produced on at least a part of the surface of the lithium composite oxide through the heat treatment in the step (e): [Chemical formula 3] Li a A b O c (where: A is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦a≦10, 0<b≦8, 2≦c≦13.
Citation Information
Patent Citations
Positive electrode active material for a lithium secondary battery containing a lithium metal oxide having a multilayer structure and a positive electrode containing the same
JP2018523895A
Precursor Synthetic method for lithium-ion secondary battery cathode active material from waste battery material, and manufacturing method of the cathode active material made by the same
KR1020170033787A